Implementation of Moral Education in Overcoming Online Game Addiction - Moch. Iqbal Zulfikar PD; Sidik Eli Lahagu; Ima Mutholliatil Badriyah; Hermi Pasmawati; Hamid Patilima; Ghina Ulpah (Institut Agama Islam An-Nawawi Purworejo, 2024)
Addiction to games occurs due to the release of substances that cause feelings of pleasure and comfort. Psychologically, the emotions of someone with online game addiction are also disturbed. In this case, moral learning can be used as a basis for change to shape character and overcome technology addiction, especially online games. This research aims to describe moral education implemented as an effort to overcome changes in students' morals due to online game addiction. The method used in this research is presented descriptively and analytically through data collection from observation, interviews, and documentation. then analyzed by reducing the data to be presented in the research results. The research results show that moral education applied to overcoming online game addiction in schools can make students focus on participating in learning activities. With supporting factors for an inclusive learning environment.